Description of adult female, larva, and pupa of Glossosoma (Lipoglossa) kamael Malicky 2012 (Trichoptera: Glossosomatidae) associated by COI sequences from China - Zang, Hao-Ming; Ge, Xin-Yu; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2022)
The adult female, larva, and pupa of Glossosoma (Lipoglossa) kamael Malicky 2012 from Qinghai Province, China, are described and illustrated. Molecular associations are based on COI sequences. The immature stages of the subgenus Lipoglossa are described for the first time. Biological and habitat information of G. kamael are presented.